Else one approach to a problem of the Okhotsk massif in the northwestern Okhotsk region; Russian Journal of Pacific Geology; Vol. 9, iss. 1 - Petrishchevsky A. M. Alexander Mitrofanovich (2015, 2015)
Title screen